Morphogenetic Responses of Winter Wheat Callus Culture Under Prolonged Period of Low-Temperature Exposure - Chumakova, Viktoriia; Avksentyeva, Olga (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 287